Pengaruh Kualitas Layanan, Kepercayaan dan Citra Klinik terhadap Loyalitas Pasien melalui Kepuasan Pasien di Klinik Pratama Kartika 0729 Bantul Yogyakarta - Anggraini, Sofia; Yuliati, Farida; Malik, Rahadian; Kosasih, Kosasih; Nugroho, Taufan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Patient loyalty is an indicator of a clinic’s success, influenced by trust, service quality, clinic image, and patient satisfaction. This study analyzes the influence of service quality, trust, and clinic image on patient loyalty through patient satisfaction at Pratama Kartika Clinic 0729 Bantul Yogyakarta. This study employs a descriptive verification method with a sample of 100 patients selected using an accidental sampling technique. Data was collected through interviews using questionnaires and analyzed using descriptive analysis and Path Analysis. The research findings indicate that service quality, trust, clinic image, patient satisfaction, and patient loyalty fall into the good category. Service quality and clinic image have a positive and significant influence on patient satisfaction, while trust has a negative and significant influence on satisfaction. Service quality and trust positively and significantly influence patient loyalty through satisfaction, whereas clinic image has a negative and significant effect on patient loyalty through satisfaction. Patient satisfaction has a positive and significant influence on patient loyalty. Recommendations for Pratama Kartika Clinic 0729 Bantul Yogyakarta include creating a service tagline, building emotional bonds with patients through excellent service, providing a digital suggestion box application, and conducting regular patient satisfaction surveys. The clinic should also evaluate its services, expand service types, implement marketing strategies, and enhance the technical skills of medical and paramedical staff to improve service quality.